Exclusion Spirometry: A Bad Idea - Andrew Mcivor (Canadian Respiratory Journal)
No single item or combination of items from the bedside clinical examination can rule out airflow obstruction; for this purpose, spirometry is essential. I, like my colleagues, visually conceptualize chronic obstructive pulmonary disease patients using objective lung function testing. I am well aware that spirometry has neither been accepted nor widely performed outside of specialist practice (1). In this issue of the Canadian Respiratory Journal, Almirall and Bégin (pages 195 to 196) provide a very reasoned argument suggesting that obtaining isolated normal values of spirometric indexes can exclude certain conditions.